1983
DOI: 10.1111/j.1432-1033.1983.tb07742.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the rearrangement of 2‐aminoethanol by ethanolamine ammonia‐lyase

Abstract: (1R)‐2‐Amino[1‐2H1]ethanol and (1S,2RS)‐2‐amino[1,2‐2H2]ethanols have been synthesised by decarboxylation of (2S,3R)‐[3‐2H1]serine and (2S,3S)‐[2,3‐2H2]serine respectively. The stereochemical integrity of these labelled 2‐aminoethanols has been ascertained from the 1H‐NMR spectra of their N,O‐dicamphanoyl derivatives. This assay has also been used to confirm that samples of (2R)‐ and (2S)‐2‐amino[2‐2H1]ethanols prepared from (2R)‐ and (2S)‐[2‐2H1]glycines are stereochemically pure. Ethanolamine ammonia‐lyase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…The data indicate that virtually all 5′-deoxyadenosine molecules contain at least one deuterium. The small quantity of the unlabeled 5′-deoxyadenosine (0.25 ( 0.02%) present is less than the 0.45-0.5% protium content in the 1-pro-S position (11,12) of the [1,1,2,2-2 H 4 ]-HEH. The model of the inactivation (see below) predicts an enrichment of unreacted HEH in protium.…”
Section: Rapid-kinetic Studies Of the Inactivation Of Eal By Hehmentioning
confidence: 99%
See 1 more Smart Citation
“…The data indicate that virtually all 5′-deoxyadenosine molecules contain at least one deuterium. The small quantity of the unlabeled 5′-deoxyadenosine (0.25 ( 0.02%) present is less than the 0.45-0.5% protium content in the 1-pro-S position (11,12) of the [1,1,2,2-2 H 4 ]-HEH. The model of the inactivation (see below) predicts an enrichment of unreacted HEH in protium.…”
Section: Rapid-kinetic Studies Of the Inactivation Of Eal By Hehmentioning
confidence: 99%
“…Experimental observations show that tritium at the 5′-position of the cofactor is discriminated against by a factor of ∼100 in transfer to product (9). This 3 H kinetic isotope effect is much larger than is expected from the deuterium isotope effect in the overall reaction ( D V ≈ 7) (9)(10)(11)(12). To rationalize these kinetic isotope effects, the presence of an alternative reaction pathway involving an enzyme-based radical has been proposed (13).…”
mentioning
confidence: 99%
“…The synthesis of [1,1-2 H 2 ]-ethanolamine 7a followed a previous protocol 12 involving the reduction of glycine methyl ester hydrochloride 11 with LiAl 2 H 4 (Scheme 4). The reaction conveniently generated the required isotopically labelled [1,1-2 H 2 ]-ethanolamine 7a in a single step.…”
Section: Resultsmentioning
confidence: 99%
“…This was evident from the substantial double labelling of the resultant metabolites after feeding experiments with [2-13 C]-glycine 5a. The recombination of the C-2 of glycine 5 is attributed to the in vivo biosynthesis of [2,[3][4][5][6][7][8][9][10][11][12][13] C]glycine 5b did not significantly label the fluorometabolites, consistent with their origin primarily from C-2 and not C-1 of glycine 5 via C-2 and C-3 of serine 6. Investigations with appropriate isotopically labelled serine, pyruvate and glycerol have indicated that these compounds were also good precursors of the fluorometabolites and it was proposed that the carbon substrate for fluorination was derived from a phosphorylated intermediate of the glycolytic pathway present between glycerol and pyruvate.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation